Metabolic Activation of Polycyclic Aromatic Hydrocarbons and Aryl and Heterocyclic Amines by Human Cytochromes P450 2A13 and 2A6 - Shimada, Tsutomu (2013)
Human cytochrome P450 (P450) 2A13 was found to interact with several polycyclic aromatic hydrocarbons (PAHs) to produce Type I binding spectra, including acenaphthene, acenaphthylene, benzo[c]phenanthrene, fluoranthene, fluoranthene-2,3-diol, and 1-nitropyrene. P450 2A6 also interacted with acenaphthene and acenaphthylene, but not with fluoranthene, fluoranthene-2,3-diol, or 1-nitropyrene. P450 1B1 is well known to oxidize many carcinogenic PAHs, and we found that several PAHs (i.e., 7,12-dimethylbenz[a]anthracene, 7,12-dimethylbenz[a]anthracene-5,6-diol, benzo[c]phenanthrene, fluoranthene, fluoranthene-2,3-diol, 5-methylchrysene, benz[a]pyrene-4,5-diol, benzo[a]pyrene-7,8-diol, 1-nitropyrene, 2-aminoanthracene, 2-aminofluorene, and 2-acetylaminofluorene) interacted with P450 1B1, producing Reverse Type I binding spectra. Metabolic activation of PAHs and aryl- and heterocyclic amines to genotoxic products was examined in Salmonella typhimurium NM2009, and we found that P450 2A13 and 2A6 (as well as P450 1B1) were able to activate several of these procarcinogens. The former two enzymes were particularly active in catalyzing 2-aminofluorene and 2-aminoanthracene activation, and molecular docking simulations supported the results with these procarcinogens, in terms of binding in the active sites of P450 2A13 and 2A6. These results suggest that P450 2A enzymes, as well as P450 Family 1 enzymes including P450 1B1, are major enzymes involved in activating PAHs and aryl- and heterocyclic amines, as well as tobacco-related nitrosamines.